Search for New Structural and Semantic Means of Organizing the Genre Form of the Sonnet to Express a Tragic Worldview - Иваненко, Виктория Анатольевна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article deals with the abilities of the poetic text stanzaic organization to convey emotionally coloured sense. The canonized form of the sonnet undergoes semantic and structural transformations in the works of English poets of the First World War period. A particular role in the integral unity of verse is played by the artistic device of perversion. English “trench poetry” serves as a source for exemplifying of adaptation capacity of architectonic, structural and semantic constituents of the canonized verse forms.